Polycrystalline para-terphenyl scintillator adopted in a β− detecting probe for radio-guided surgery. (May 2015) - Solfaroli Camillocci, E; Bellini, F; Bocci, V; Collamati, F; De Lucia, E; Faccini, R; Marafini, M; Mattei, I; Morganti, S; Paramatti, R; Patera, V; Pinci, D; et al.
Abstract: A radio-guided surgery technique exploiting β − emitters is under development. It aims at a higher target-to-background activity ratio implying both a smaller radiopharmaceutical activity and the possibility of extending the technique to cases with a large uptake of surrounding healthy organs. Such technique requires a dedicated intraoperative probe detecting β - radiation. A first prototype has been developed relying on the low density and high light yield of the diphenylbutadiene doped para-therphenyl organic scintillator. The scintillation light produced in a cylindrical crystal, 5 mm in diameter and 3 mm in height, is guided to a photo-multiplier tube by optical fibres. The custom readout electronics is designed to optimize its usage in terms of feedback to the surgeon, portability and remote monitoring of the signal. Tests show that with a radiotracer activity comparable to those administered for diagnostic purposes the developed probe can detect a 0.1 ml cancerous residual of meningioma in a few seconds.